Optimization of transportation systems - Borndörfer, Ralf 1967-; Grötschel, Martin 1948-; Löbel, Andreas 1967- (Konrad-Zuse-Zentrum für Informationstechnik, 1998)
Abstract: "The world has experienced two hundred years of unprecedented advances in vehicle technology, transport system development, and traffic network extension. Technical progress continues but seems to have reached some limits. Congestion, pollution, and increasing costs have created, in some parts of the world, a climate of hostility against transportation technology. Mobility, however, is still increasing. What can be done? There is no panacea. Interdisciplinary cooperation is necessary, and we are going to argue in this paper that Mathematics can contribute significantly to the solution of some of the problems. We propose to employ methods developed in the Theory of Optimization to make better use of resources and existing technology. One way of optimization is better planning. We will point out that Discrete Mathematics provides a suitable framework for planning decisions within transportation systems. The mathematical approach leads to a better understanding of problems. Precise and quantitative models, and advanced mathematical tools allow for provable and reproducible conclusions. Modern computing equipment is suited to put such methods into practice. At present, mathematical methods contribute, in particular, to the solution of various problems of operational planning. We report about encouraging results achieved so far."
Auch in: Acta Forum Engelberg 1998
Keywords: Informatik; Mathematik; Computer science -- Mathematics; Mathematical optimization; Transportation -- Planning; Verkehrssystem; Optimierung